The Influence of General Allocation Funds and Special Allocation Funds on the Human Development Index in Bima Regency - Arif Rizki; Muhammad Kadarisman; Ari Juliana; Syati Irawati; Reza Fitriansyah (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The government's active role in improving national development is by exploring national and regional revenues to be able to finance government activities and programs to support the entire development process. Bima Regency is one of the regions in West Nusa Tenggara that has not been optimal in implementing development. For this reason, the focus of this research is the influence of private sector involvement seen from indicators of gross regional domestic product, while the objectives of this research are (a) to know and analyze the influence of the General Alakosi Fund partially on the Human Development Index, (b) to know and analyze the influence of the Special Alakosi Fund partially on the Human Development Index, (c) knowing and analyzing the influence of the General Alakosi Fund and the Special Allocation Fund integrally on the Human Development Index. (d) knowing and analyzing the biggest influence of the special allocation fund on the human development index. This research uses a quantitative paradigm. This type of research is comparative causal research. The population in this research consists of secondary data regarding DAU and DAK reports during the establishment of the Bima Regency Government, especially in the implementation of regional autonomy and Human Development Index Data, sampling was carried out based on Purposive Cluster Sampling. Data Analysis Methods and Techniques used classical assumption test, multiple regression analysis, multiple correlation analysis, coefficient of determination analysis and statistical significance test analysis. The research results show that (1) there is an influence of general allocation funds from the variables calculated on the human development index. (2) there is a negative influence of allocation funds specifically on the human development index. (3) there is a simultaneous influence between general allocation funds and special allocation funds on the human development index. Conclusion. The results of data calculations using calculation methods that are in accordance with research show that there is a significant influence on general allocation funds and special allocation to the human development index in Bima district. This research not only provides practical recommendations for local governments, but also enriches the academic literature with new findings that are relevant for regional economic and development studies.